Examining the Admissibility or Otherwise of Evidence Generated from Closed-Circuit Television (CCTV) and Deoxyribonucleic Acid (DNA) Test as Means of Proof of Zina Under Islamic Law - Abikan, Yahaya Ibrahim (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This article examines the admissibility of evidence generated from CCTV and DNA tests as a means of proving adultery according to Islamic Law with a critical and argumentative study. This article reveals that hadd punishment cannot be imposed based on evidence generated from CCTV and DNA tests because the admission of such evidence will erode and neutralize the Qur'anic requirement of four reliable eyewitnesses before punishment. On the other hand, such evidence cannot be used to replace the provisions of the Qur'an and Sunnah because they are circumstantial and therefore subject to doubt. The author's main finding is that the only acceptable evidence for adultery is that prescribed by the Qur'ān or Sunnah, namely the oral testimony of four reliable eyewitnesses and confession. The article recommends that evidence generated from CCTV and DNA tests should be good evidence and equally admissible in all non-hudud offenses especially when there is no human interference or interruption tainting or affecting the evidence.